The behaviour of travellers in the transition to responsible tourism: the case of the Baltic Sea Region - Šimanskienė, Ligita; Labanauskaitė, Daiva; Montvydaitė, Deimena (Business: Theory and Practice, 2022)
Changes in travellers’ behaviour are among the most significant issues in the recent revolution of the tourism industry. The perception of perceived value and quality lead to rethinking priorities and choices while travelling. The purpose of the article is to analyse the expression of travellers’ behaviour orientation towards the key elements of responsible tourism in the countries of the Baltic Sea Region. The findings of quantitative research, which has been carried out in the form of survey, reveal that the behaviour of travellers of the Baltic Sea Region confirms that responsible tourism has become a way of thinking. The transition to responsible tourism is primarily driven by tourism destination-related elements and the strength of the impact related to maintaining the quality of life of local people, redistributing the benefits of tourism for travel destinations, enhancing the value and distinctiveness of the travel destination product, and maintaining long-term attractiveness, within the capacity of the travel destination and efficient use of its tourism resources. It may be the direction towards more sustainable and responsible future of traveling.